Optical coherence tomography angiography in patients with focal epilepsy - Rider, Flora; Guekht, Alla; Shpak, Alexander (Frontiers in Neurology, 2025)
PurposeThis study aims to compare optical coherence tomography angiography (OCTA) data in individuals with focal epilepsy and healthy individuals and to investigate the effect of antiseizure medications (ASM) on OCTA data.MethodsWe examined 48 consecutive patients with focal epilepsy and 46 healthy controls. Area and skeleton density of superficial and deep capillary plexuses in the macular area and peripapillary radial capillary plexus were measured.ResultsIn general, no differences in OCTA parameters were found between groups of individuals with epilepsy and healthy individuals. A comparison of individuals with epilepsy with and without comorbid major depressive disorder revealed no differences in OCTA data. However, the area and skeleton densities of the perfused capillary retinal vascular bed in the macular region showed a negative association with the use of valproates and modifiers of the presynaptic release machinery, whereas only the skeleton density of the deep capillary plexus showed a positive association with the use of modulators of voltage-gated sodium channels.ConclusionOCTA revealed different effects of various ASM groups on the perfused macular capillary bed. These findings suggest that OCTA parameters could serve as potential biomarkers for assessing ASM effects on small vessels and capillaries in the brain.